CALCIFICATION AND ATHEROSCLEROSIS OF THE CORONARY ARTERIES - Abdullaev Ikrom Abduvalievich (Journal Park Publishing, 2023)
Calcification is a very common occurrence in coronary arteries as part of the atherosclerotic process, and the degree of calcification may predict clinical outcomes in patients at high risk of coronary events. Both the degree of calcification and the patterns of its distribution are of prognostic value, but the relationship between coronary artery calcification and atherosclerotic plaque instability is extremely complex and not fully understood. This article is devoted to the study of calcification markers and their influence on the development of an atherosclerotic focus.
Keywords: coronary atherosclerosis, atherosclerotic plaque, calcification markers.